2013
DOI: 10.1890/es13-00094.1
|View full text |Cite
|
Sign up to set email alerts
|

Biological control and precipitation effects on spotted knapweed (Centaurea stoebe): empirical and modeling results

Abstract: Abstract. The literature is inconsistent regarding the ability of herbivory to control or reduce densities of a major invasive plant species of North America, spotted knapweed (Centaurea stoebe). Here, findings from experimental manipulations of spotted knapweed and long-term monitoring of seed production and insect abundance were used to parameterize a population matrix model for this species. Model predictions were compared against spotted knapweed densities observed in permanent transects, which were establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Our model selection procedure, however, indicated that precipitation and herbivory do not interact at the landscape scalea result also consistent with biological control of spotted knapweed [Centaura stoebe L. subsp. micranthos (Gugler) Hayek] in Colorado USA (Maines, Knochel & Seastedt 2013). Other analyses have also revealed that precipitation does not indirectly affect landscape-scale population growth of M. janthiniformis (A.S. Weed, unpublished data).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our model selection procedure, however, indicated that precipitation and herbivory do not interact at the landscape scalea result also consistent with biological control of spotted knapweed [Centaura stoebe L. subsp. micranthos (Gugler) Hayek] in Colorado USA (Maines, Knochel & Seastedt 2013). Other analyses have also revealed that precipitation does not indirectly affect landscape-scale population growth of M. janthiniformis (A.S. Weed, unpublished data).…”
Section: Discussionmentioning
confidence: 94%
“…subsp. micranthos (Gugler) Hayek] in Colorado USA (Maines, Knochel & Seastedt ). Other analyses have also revealed that precipitation does not indirectly affect landscape‐scale population growth of M. janthiniformis (A.S. Weed, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…While many other studies find that invasive plants accumulate enemies in their invaded range (Liu & Stiling, ), it is rare that an exotic specialist enemy is present without purposeful introduction (but see Chang, Blakeslee, Miller, & Ruiz, ; Morrison & Hay, ; Stricker & Stiling, ). Typically, specialist herbivores, such as A. aurea , are introduced as biological control (DeWalt, ; Maines, Knochel, & Seastedt, ). In our study, a specialist herbivore does not significantly decrease population growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…Drought‐induced changes in herbivore performance and plant tolerance could have wide‐reaching implications for weed biological control. Drought could either increase or decrease the impacts of weed biological control agents; the combined effects of drought stress and herbivory on plant fitness could be stronger or weaker than would be expected from their individual impacts (Willis et al, 1993; Maines et al, 2013). For example, drought‐stressed Opuntia aurantiaca Lindl .…”
Section: Introductionmentioning
confidence: 99%